Pengaruh Current Ratio (CR) Dan Debt To Equity Ratio (DER) Terhadap Net Profit Margin (NPM) Pada PT Indofarma Tbk Periode 2014-2023 - Rizal Lesmana; Ayu Puspa Lestiyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Net Profit Margin (NPM) at PT Indofarma Tbk. The research method uses a quantitative approach with secondary data in the form of annual financial reports for the period 2014–2023. The analysis used descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and the coefficient of determination with the help of SPSS 26. The results showed that the Current Ratio did not have a significant effect on the Net Profit Margin, with a significance value of 0.990 > 0.05 and a t-value (0.13) < t-table (2.306). Conversely, the Debt to Equity Ratio has a significant negative effect on Net Profit Margin, with a significance value of 0.001 < 0.05 and t count (-5.891) > t table (2.306). Simultaneously, CR and DER have a significant effect on NPM with a significance value of 0.000 < 0.05. The coefficient of determination shows that CR and DER contribute 88% to the variation in NPM, while 12% is influenced by other factors outside this study. These findings confirm that capital structure, particularly DER, plays a more dominant role in influencing company profitability.